KEPEMIMPINAN MAJELIS RESORT GEREJA KALIMANTAN EVANGELIS (GKE) DI KALIMANTAN SELATAN MASA PANDEMI COVID-19 - Kinurung maleh; Sudianto; Yusak Kurniawan (Unit Penerbitan Informasi dan Teknologi Sekolah Tinggi Teologi Gereja Kalimantan Evangelis (STT GKE), 2021)
This article is based-research rooted in the reality and impact of Pandemic Coronavirus Disease 2019 (COVID-19) worldwide from the beginning of 2020. The Pandemic has changed and harmed many aspects of life: health, social culture, economy, politic, education, and religion: killing 1,8 million people and infecting 83 million people in 222 countries. The impacts of the Pandemic have also come to Kalimantan Island - Indonesia as the mission field of GKE. Considering the various impacts of the Pandemic, the mission and wisdom of the GKE District Board (Majelis Resort GKE) are very urgent and helpful to overcome the Pandemic. The capacity of the quick and right response to the crucial situation proves the excellence and quality of the GKE District Board Leadership (MRGKE). The Board has developed creativity, innovation, and contextualization of ministry as pieces of evidence of church leaders during the Pandemic. Doing ministries on virtual worship for the availability of internet access in some congregations, yet home visitation as part of worship in other congregations. Practicing virtual meetings, WA-Call pastoral, creative fund-raising for the change of financial condition, the new adaptation of social and ethical attitude by physical distancing and health protocol. The GKE Districts have struggled within their dynamic life: on their strength and weakness. The pandemic reality and leadership dynamics of the District Board were processed through qualitative research with the methods of collecting data by interviews and resource study. The process of description and analysis were conducted by descriptive technique: the data of research classified within categorized within a parallel pattern then described within the similar themes. The final analysis anchors to the six solving – a recommendation to the Leadership (Leader) of GKE District Board (both in Pandemic time or Normal): the intensity and creativity of worship, the effectivity of face-by-face encounter, the mastering and application of technology, new fund-raising and creative financial source, the strengthening of pastoral and diaconal ministry, and the development of networking.